How Do Hospital-Specific Data Dictionaries Impact Competency Level With Data Collection: A National Survey. Issue 6 (November 2022) - Urban, Shane; Carmichael, Heather; Vasilatos, Angela; Moe, Martin; Dumond, Robbie; Kennard, Lori; Vega, Stephanie; Krell, Regina; Cripps, Michael W.; Velopulos, Catherine
Abstract : Background: Trauma registry staff are tasked with high-quality data collection to support program requirements. Hospital-specific data dictionaries are increasingly used to ensure accurate data collection, yet it is unknown how such a resource impacts a trauma registry team's competency with data collection. Objective: This study sought to explore whether having a hospital-specific data dictionary affected trauma service team members' self-reported competency level with abstracting required and nonrequired data elements. Methods: This study used an anonymous, cross-sectional survey distributed (July 2020 to September 2020) by the Society of Trauma Nurses, the American College of Surgeons, and the Trauma System News outlets to trauma registrars, trauma nurse coordinators, clinical quality specialists, program managers, program directors, and trauma research personnel. A 26-question survey was designed using a visual sliding scale from 0 to 100 to measure self-reported competence and associated variables. Results: A total of 881 respondents completed the survey from at least 495 centers. Six hundred ninety-six (79.0%) respondents were from Level I or Level II programs. Several factors were associated with team members feeling highly competent in collecting data for various reporting requirements, including the level of trauma center verification, tenure working in trauma services, and the presence of a hospital-specific data dictionary. Conclusion: Trauma centers should consider establishing a hospital-specific data dictionary as they are associated with higher registry staff competence working with trauma registry data.